Development of Critical Thinking Skills in Modern Islamic Boarding School - Azmi Zarkasyi; Defi Firmansah; Thoriq Majid Rahmadias (Yayasan Letiges Konsultan Sosial, 2024)
This research analyses the development of critical thinking skills in activities organized by academic forums at the Gontor Modern Boarding School. Using a qualitative case study approach, data was collected through interviews, observation and documentation. Analysis in three stages collection, reduction, and verification. The findings of this study highlight the importance of critical thinking, which is essential for higher-order cognitive skills and education at all levels. Gontor Islamic Boarding School which accommodates various groups such as the ITQAN (Ilmi, Tarbawy, Qur'any) Group, an academic forum, prioritizes the development of critical thinking skills, placing great emphasis on fostering critical thinking through various activities including scientific discussions, critical reading, observation, cultivating a sense of be curious, and encourage reflection. These activities improve analytical and synthesis skills, problem-solving abilities, inference and evaluation skills, and explanation skills, thereby enabling strategic thinking among students. This study also identified several supporting factors, such as a conducive scientific environment and supportive supervisors, and inhibiting factors such as administrator competency problems, low student involvement, irregular scheduling, and inadequate facilities. In particular, this research uniquely focuses on explaining 12 indicators of critical thinking abilities, which are categorized into 5 aspects according to Robert Ennis. Despite the challenges, this illustrates how Gontor developed these aspects in the ITQAN Group (Ilmi, Tarbawy, Qur'any) by highlighting inhibiting and supporting factors.